Perawatan Mesin Crusher Menggunakan Metode RCM dan MVSM di PT. Galatta Lestarindo Sijunjung - Meldia Fitri; Mohammad Farid; Hermanto (Universitas Putra Indonesia YPTK Padang, 2023)
PT. Gallata Lestarindo, which is located across Sumatra, Sei Lansek, Kec. Kamang Baru, West Sumatra which is committed to providing quality and useful products, namely the manufacture of organic fertilizer from dolmite stone or limestone, PT. Gallata Lestarindo Recognized as a growing, superior and trusted World Class Company as a fertilizer supplier, with the main focus on customer satisfaction. Based on preliminary observations made at PT. Galatta Leastarindo Sijunjung. While carrying out research at PT. Galatta Leastarindo Sijunjung, the crusher machine was often damaged which resulted in delays in the production process. Based on the problems above, this research was made to solve the problem of crusher machine maintenance using the Reliability Centered Maintenance (RCM) method and Maintenance Value Stream Map (MVSM) with Failure Modes and Effect Analysis (FMEA) calculations in an effort to increase production targets for smoothness in processing minerals, especially in mines dolomite rock. the results of maintenance intervals in 1 (one) month the company must provide time for maintenance on the machine with time on unit 1 for 82,24 hours, unit 2 for 29,72 hours and unit 3 for 2,82 hours.